Amorphous silicon carbon films prepared by hybrid plasma enhanced chemical vapor/sputtering deposition system: Effects of r.f. Power - Rashid, N.M.A.; Ritikos, R.; Othman, M.; Khanis, N.H.; Gani, S.M.A.; Muhamad, M.R.; Rahman, S.A. (2013)
Silicon carbon films were deposited using a hybrid radio frequency (r.f.) plasma enhanced chemical vapor deposition (PECVD)/sputtering deposition system at different r.f. powers. This deposition system combines the advantages of r.f. PECVD and sputtering techniques for the deposition of silicon carbon films with the added advantage of eliminating the use of highly toxic silane gas in the deposition process. Silicon (Si) atoms were sputtered from a pure amorphous silicon (a-Si) target by argon (Ar) ions and carbon (C) atoms were incorporated into the film from C based growth radicals generated through the discharge of methane (CH4) gas. The effects of r.f. powers of 60, 80, 100, 120 and 150 W applied during the deposition process on the structural and optical properties of the films were investigated. Raman spectroscopic studies showed that the silicon carbon films contain amorphous silicon carbide (SiC) and amorphous carbon (a-C) phases. The r.f. power showed significant influence on the C incorporation in the film structure. The a-C phases became more ordered in films with high C incorporation in the film structure. These films also produced high photoluminescence emission intensity at around 600 nm wavelength as a result of quantum confinement effects from the presence of sp2 C clusters embedded in the a-SiC and a-C phases in the films. Â© 2012 Elsevier B.V.